Pengaruh Penambahan Kupang dan Proporsi Ayam : Tepung Mocaf terhadap Tingkat Kesukaan Xiao Long Bao - Ellena Talitha Philotheon; Asrul Bahar; Nugrahani Astuti; Ila Huda Puspita Dewi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Xiao Long Bao is known for its uniqueness in serving soup inside dumplings. This study aims to: 1) determine the effect of the addition of mussels and the proportion of chicken: mocaf flour on the level of xiao long bao's preference; 2) determine the interaction between the addition of mussels and the proportion of chicken: mocaf flour on the level of xiao long bao's preference; 3) determine the nutritional content of xiao long bao with the addition of mussels and the proportion of chicken: mocaf flourbest. The research method used was in the form of a preference test with 50 panelists. Data analysis was carried out using the two way anova test and the Duncan test. The best Xiao long bao will be tested for its nutrient content in laboratory tests. The results of the study showed that: 1) products with the addition of 15% mussels and chicken proportions: mocaf flour of 90%:10% is preferred based on color, aroma, texture taste and chewiness; 2) the interaction of the addition of mussels and the proportion of chicken: mocaf flour has a real effect on the finished color, aroma, taste, and texture of xiao long bao, but it does not have a real effect on the finished result of xiao long bao's chewiness; 3) The results of the Xiao Long Bao laboratory test with the addition of 15% mussels and the proportion of chicken: Mocaf flour 90%:10% has a carbohydrate content of 51.12%, protein 7.85%, fat 3.82%, and calcium 185.20%.